2019
DOI: 10.1007/s00068-019-01078-5
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of the column concept in the operative management of posterior column tibial plateau fractures

Abstract: Introduction: The three-column concept has been proposed as tool in surgical decision making for treating tibial plateau fractures. Recent studies have underscored the negative effect of posterior column tibial plateau fractures on clinical outcome. The purpose of this study was to assess the value of the three column concept and posterior plating in posterior column fractures. We hypothesized that treating patients according to the three-column concept improves functional outcome. Methods: 111 consecutive tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Common comorbidities, such as type II diabetes or arterial hypertension, have not been associated with clinical outcomes [ 6 , 7 , 10 ]. However, reports analyzing the risk factors of bone metabolism in a cohort of TPF are rare.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Common comorbidities, such as type II diabetes or arterial hypertension, have not been associated with clinical outcomes [ 6 , 7 , 10 ]. However, reports analyzing the risk factors of bone metabolism in a cohort of TPF are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies that have analyzed the outcome of TPF have identified several risk factors for poor clinical and radiological outcome, such as fracture complexity, leg axis malreduction [ 9 ], involvement of the posterior column [ 7 ], residual articular depression of more than 2 mm [ 9 , 13 ], or postoperative malreduction due to an impaired intraoperative fragment visualization [ 26 , 49 ], while the impact of associated soft-tissue injuries is still under debate [ 50 , 51 ]. In the individual failure analysis of the present study, two of six cases may be explained solely by a potential IBM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations